Development of Interactive Digital Learning Media To Improve Science Literacy and Learning outcomes of Elementary School Students In Natural And Social Sciences (IPAS) In Enrekang Regency - Saleha; Baso Jabu; Nurhikmah H (Indonesian Journal Publisher, 2025)
This study aimed to develop an interactive digital learning medium based on Articulate Storyline that is valid, practical, and effective in improving scientific literacy and learning outcomes of fifth-grade elementary students in Enrekang Regency. The research employed a Research and Development design using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. Research subjects consisted of teachers and fifth-grade students from several elementary schools representing different geographical conditions. Data were collected through expert validation, practicality questionnaires, and learning achievement tests, then analyzed using descriptive and inferential statistics, including paired sample t-tests and N-Gain analysis. The results show that the developed learning media achieved high validity according to expert assessments, demonstrated good practicality in classroom implementation, and effectively improved students’ scientific literacy and learning outcomes. Thus, the interactive digital learning medium serves as an innovative instructional tool aligned with the Merdeka Curriculum, promoting active and meaningful science learning experiences for elementary